Dealing With Negative Workplace Gossip: From the Perspective of Face - Zong, Boqiang; Xu, Shiyong; Zhang, Lihua; Qu, Jinzhao (Frontiers in Psychology, 2021)
In this paper, we investigate the coping response of the individuals who are being gossiped about. Drawing on the face research and affective events theory (AET), we propose that employees who are the targets of negative gossip will actively respond the gossip about them via engagement in negative gossip themselves. Findings showed that negative workplace gossip stimulated the fear of losing face and led to subsequent behavioral responses—namely, engaging in negative gossip. Moreover, self-monitoring, as a moderating mechanism, mitigated the negative impacts of negative workplace gossip on the targets. We discuss the theoretical implications for gossip research, and note its important practical implications.